Visual transmission of information as cognitive stimulus of the creative process - Rivera, Javier; Vidal, Rosario; Chulvi, Vicente; Lloveras, Joaquim (Anales de Psicología / Annals of Psychology, 2010)
Technological surveillance, intelligence and prospective tech-niques seek to capture, assimilate and apply knowledge, often making use of diagrams. An experimental study was set up to learn how knowledge transfer can stimulate or obstruct the creative process. The state of the art was assessed, and new ways to visually represent knowledge and incre-ment the quality and quantity of individual and collective inputs through-out the different stages of the creative process were sought. The impact of the different types of diagrams was measured using the CREA creative intelligence test. The connection type diagram, which is the least frequent, was found to yield the better results in terms of creativity stimulation. The analysis of two case studies to find alternatives for the development of products, processes and technology services confirms the good results obtained by combining the Delphi method (for prospective purposes), and mental maps as instances of diagrams with a connected structure.